รูปแบบการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัด ตามหลักเทวธรรมในการอนุรักษ์ป่าภาคใต้ตอนบน The Model of Consciousness Development for Personnel in Provincial Administrative Organiz ation with Dewathamma for Forest Conservation in - วงศ์ณาศรี ปัณณพงศ์ (Academic Journal Phranakhon Rajabhat University, 2017)
บทคัดย่อ การวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อศึกษา 1) วิเคราะห์สถานการณ์จิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรมในการอนุรักษ์ป่า ภาคใต้ตอนบน 2) สร้างรูปแบบการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรมในการอนุรักษ์ป่าภาคใต้ตอนบน และ 3) ประเมินรูปแบบการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรม ในการอนุรักษ์ป่า ภาคใต้ตอนบน โดยเลือกพื้นที่ในการศึกษา คือ องค์การบริหารส่วนจังหวัดกระบี่ การวิจัยเรื่องนี้เป็นการวิจัยโดยผสมผสานวิธีวิจัยเชิงคุณภาพ และวิธีวิจัยเชิงปริมาณ โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพเป็นหลัก โดยการสัมภาษณ์เชิงลึก จำนวน 9 คน และการสนทนากลุ่ม จำนวน 6 คน เครื่องมือที่ใช้ในการวิจัยคือ 1) แบบสัมภาษณ์เชิงลึกแบบมีโครงสร้าง และ 2) แบบสนทนากลุ่ม วิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหา และการวิจัยเชิงปริมาณ ประชากร รวมทั้งสิ้น 259 คน กลุ่มตัวอย่าง จำนวน 15 คน วิธีการสุ่มตัวอย่างแบบเชิงชั้นตามอัตราส่วน และการสุ่มตัวอย่างแบบง่าย เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถามแบบมีโครงสร้าง วิเคราะห์ข้อมูลโดยใช้โปรแกรมคอมพิวเตอร์ทางสถิติ และสถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย และค่าส่วนเบี่ยงเบนมาตรฐาน ผลการศึกษาพบว่า 1. การสำรวจสถานการณ์จิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรมในการอนุรักษ์ป่า ภาคใต้ตอนบน โดยภาพรวมของการการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรมในการอนุรักษ์ป่าภาคใต้ตอนบน อยู่ในระดับน้อยทุกด้าน ค่าเฉลี่ย 2.51 ทั้งด้านโทษของการทำลายป่า อยู่ในระดับน้อย มีค่าเฉลี่ย 2.52 ด้านกฎแห่งกรรม อยู่ในระดับน้อย มีค่าเฉลี่ย 2.27 และด้านการพัฒนาจิตสำนึก อยู่ในระดับน้อย มีค่าเฉลี่ย 2.51 2. รูปแบบการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรมในการอนุรักษ์ป่าภาคใต้ตอนบน คือ CSR MODEL ได้แก่ 1) C ย่อมาจาก Collective Consciousness อยู่ในโครงสร้างส่วนบนของรูปแบบ หมายถึง จิตสำนึกร่วมของบุคลากรองค์การบริหารส่วนจังหวัดตามหลักเทวธรรม ในการอนุรักษ์ป่าภาคใต้ตอนบน โดยมีการกำหนดเขตพื้นที่อนุรักษ์ป่า (Zoning) ตรงตามหลักเทวธรรม ในด้านหิริ หรือความละอายต่อบาป 2) S ย่อมาจาก Sustainable Growth อยู่ในโครงสร้างจุดศูนย์กลางของรูปแบบ หมายถึง การพัฒนาอย่างยั่งยืน ในที่นี่ หมายถึง การมีจิตสำนึกในการอนุรักษ์ป่าตามหลักเทว ธรรมของบุคลากรองค์การบริหารส่วนจังหวัดในการอนุรักษ์ป่า ภาคใต้ตอนบน ทั้งตามหลักหิริ และตามหลักโอตตัปปะ หมายถึง การเกรงกลัวต่อบาป จากโครงสร้างส่วนบนและส่วนล่าง นำไปสู่เป้าหมายสูงสุด คือการพัฒนาอย่างยั่งยืน 3) R ย่อมาจาก Responsibility อยู่ในโครงสร้างส่วนล่างของรูปแบบ หมายถึง ความรับผิดชอบของบุคลากรองค์การบริหารส่วนจังหวัดในการอนุรักษ์ป่าภาคใต้ตอนบน โดยการประชุมเชิงปฏิบัติการของบุคลากรในการพัฒนาจิตสำนึกในการอนุรักษ์ป่า ตรงตามหลักเทวธรรม ในด้านโอตตัปปะ หรือความเกรงกลัวต่อบาป 3. การประเมินผลรูปแบบการพัฒนาจิตสำนึกในการอนุรักษ์ป่าของบุคลากรองค์การบริหารส่วนจังหวัด ภาคใต้ตอนบน ตามรูปแบบ CSR MODEL นั้น มีความเหมาะสมทั้งในด้านโครงสร้าง เนื้อหา และกระบวนการ ที่มีความครอบคลุมองค์ประกอบตามหลักเทวธรรม ทั้งด้านโทษของการทำลายป่า ด้านกฎแห่งกรรม และด้านการพัฒนาจิตสำนึกของบุคลากรองค์การบริหารส่วนจังหวัด Abstract The purposes of this research were to study: 1) to analyze the situation of personnel consciousness in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern., 2) to create the model of consciousness development for personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern and 3) to evaluate the model of consciousness development for personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern. The selected area is Krabi provincial administrative organization. Research methodology by used mixed methodologies of quantitative and qualitative research. Used by the main qualitative research methodology, Key informants by using in-depth interviewfor 9 persons and 6 persons for focus group discussion. The research instruments were 1) Structured-Interview form and 2)focus group discussion form. Data were analyzed by content analysis. And in quantitative research population was total for 259 persons. Sample size was 15 persons. Sampling Method was Proportional Stratified Sampling and Sample Random Sampling.The research instruments were structured-questionnaire. The data were analyzed by using computer software package. the statistics used in data analysis were average and standard deviation. The results were as follows: 1. The consciousness development for personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern by overall is in the low level in average 2.51, the punishment of deforestation is in the low level in average 2.52, reciprocal deeds is in the low level in average 2.27 and the consciousness development is in the low level in average 2.57. 2. The model of consciousness development for personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern is called “CSR MODEL” The Letter “C” is called Collective Consciousness is in the upper structure of the model which is Collective Consciousness of personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern with setting the conservative zoning for personnel (Zoning). It is relevant to Dewathamma of shamed of sin. The Letter “S” is called Sustainable Growth is in the center structure of the model which is the consciousness development for personnel in Provincial Administrative Organization with Dewathamma both of shamed of sin and feared of sin for Forest Conservation in Upper-Southern. It is collective from upper and lower structure which go to the ultimate goal that is Sustainable Growth. The Letter “R” is called Responsibility is in the lower structure of the model which is the responsible of the personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern with workshop for develop the consciousness of personnel for Forest Conservation. It is relevant to Dewathamma of feared of sin 3. The evaluation for the model of consciousness development for personnel in Provincial Administrative Organization with Dewathamma for Forest Conservation in Upper-Southern found that appropriate in structure, contents and processes.